Feasibility Analysis Of Implementation Of SNI 3144:2015 On Tempe Products - Mauluddin, Yusuf; Kurniawati, Rina; Delfiana, Heby (UNIVERSITAS PAKUAN, 2019)
A product must have good quality by maintaining or improving its quality to satisfy customers. Good quality tempeh products must meet the standards of SNI 314:2015. Many Tempeh Small and Medium Enterprises (SMEs) still have been unable to meet it. This study aims to determine the production process that meets the quality requirements of SNI 3144:2015 and is feasible for use as a business. The method used is to compare local tempeh SMEs with tempeh entrepreneurs certified by SNI 3144:2015, as well as laboratory testing. For business feasibility analysis, the aspects analyzed are organizational and management, market and marketing, technical, environmental, legal, and financial aspects. The study results indicate that the quality of tempeh produced by local SMEs has met four of the eight SNI 3144:2015 standards. In the technical aspect, namely the production process, it is necessary to provide wet and dry areas for the production process. Wet area for processes that use much water such as boiling, soaking, breaking soybeans, washing, separating the skin, watering with warm water, cooking, rewashing, and fermentation. Dry area for packaging and fermentation process for tempeh production. The results of the business feasibility analysis, especially in the marketing aspect, show that the best scenario for SMEs is to combine marketing of SNI tempeh products and products without SNI to reach a larger market. The financial aspect analysis shows that Tempeh SMEs with SNI are feasible to run with NVP and IRR values that meet the requirements, and the investment return period is 1 Year 6 Months 19 Days.